Development of small-scale fisheries and aquaculture ontology - Tusnuva, Jahan (2021)
This Master thesis concludes a period of 6 months of internship in the framework of the Master2 EURAMA at INP Purpan School, Toulouse, for the project the “Development of small-scale fisheries and Aquaculture ontology” of the Alliance Bioversity-CIAT and WorldFish. WorldFish proposed to start an ontology for two domains: Small-scale Fisheries and Aquaculture. The objective of the ontology project is to improve the WorldFish data interoperability into the various projects, databases and repositories by (a) addressing inconsistent use of fish, fisheries, and aquaculture related terms across the datasets, (b) highlighting the missing terms in the main semantic resources, and lastly (c) connect and collaborate with the Community of Practice. The thesis describes the steps taken to a) extract the concepts used in WorldFish reporitoy and in papers published by scientists, b) identify the corresponding terms in the FAO thesaurs AGROVOC and get the termIDs, c) allocate valid defintions, d) develop the knowledge model and the ontology using Protégé.